Alcohol Consumption, Heavy Drinking, and Mortality: Rethinking the J‐Shaped Curve. (27th August 2013) - Plunk, Andrew D.; Syed‐Mohammed, Husham; Cavazos‐Rehg, Patricia; Bierut, Laura J.; Grucza, Richard A.
<x xml:space="preserve">Abstract</x> Background High average daily consumption of alcohol has been associated with elevated mortality risk, but more moderate consumption, relative to abstinence, has been associated with reduced mortality risk. However, average daily consumption can be complicated to assess, limiting its usefulness in both research and clinical practice. There are also concerns that average consumption fails to capture the risk associated with certain drinking patterns, such as heavy episodic drinking. This study assessed mortality associated with drinking pattern, operationalized as the frequency of both heavy and nonheavy drinking occasions. Methods Data from the 1997 to 2001 administrations of the National Health Interview Survey (NHIS; n = 111, 511) were paired with the current release of the NHIS Linked Mortality Files, which provided mortality follow‐up data through the end of 2006. We estimated the impact of drinking pattern on all‐cause mortality, operationalized as the frequency of heavy (5+ drinks) and nonheavy (<5 drinks) drinking occasions. Other covariates in the model included survey wave, sex, age, race/ethnicity, ratio of family income to poverty threshold, educational attainment, body mass index, and smoking status. Results Over a third of past‐year drinkers reported heavy drinking. Mortality risk increased steadily as heavy drinking frequency increased; daily heavy drinkers exhibited an almost 2‐fold risk of death compared with abstainers (p < 0.001). Regular nonheavy drinking was associated with decreased mortality, similar to the "J‐shaped curve" highlighted in past research on alcohol mortality; this potential protective effect peaked around 2 nonheavy occasions per week. Conclusions Any heavy drinking likely elevates mortality risk, and substantial health benefits could be realized by reducing heavy drinking occasions or limiting overall drinking. Heavy and nonheavy drinking frequencies are valid targets for clinical screening and could be helpful in assessing risk and promoting less harmful drinking behavior.